2019
DOI: 10.1007/s42770-019-00133-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, virulence characterization, and genetic relatedness of Listeria monocytogenes isolated from chicken retail points and poultry slaughterhouses in Turkey

Abstract: Listeria monocytogenes is one of the most important foodborne pathogens and is a causal agent of listeriosis in humans and animals. The aim of this study was to determine the prevalence, serogroups, antibiotic susceptibility, virulence factor genes, and genetic relatedness of L. monocytogenes strains isolated from 500 poultry samples in Turkey. The isolation sources of 103 L. monocytogenes strains were retail markets (n = 100) and slaughterhouses (n = 3). L. monocytogenes strains were identified as serogroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
(96 reference statements)
3
4
0
Order By: Relevance
“…The authors serogrouped 103 isolates originating from poultry samples from the retail markets and slaughterhouses in Turkey. However, the of L. monocytogenes strains (78 samples -75.7 %) were characterised as the IIa serogroup (which is in agreement with our findings), followed by the IIc serogroup (15 samples -14.5 %) and the IIb group (6 samples -5.8 %) [7].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The authors serogrouped 103 isolates originating from poultry samples from the retail markets and slaughterhouses in Turkey. However, the of L. monocytogenes strains (78 samples -75.7 %) were characterised as the IIa serogroup (which is in agreement with our findings), followed by the IIc serogroup (15 samples -14.5 %) and the IIb group (6 samples -5.8 %) [7].…”
Section: Resultssupporting
confidence: 92%
“…That study demonstrated that the 1/2a serotype was the most commonly prevalent in food products, however, the authors did not detect any isolate which belonged to the 4b, 4d or 4e serovars, whereas in our case, the IVb serogroup was the second most common. Similarly to findings of Wang et al [22], according to Coban et al [7], who used the protocol of Doumith et al [9], the IVb serogroup was the least numerous (1 sample -1.0 %) in their study. The authors serogrouped 103 isolates originating from poultry samples from the retail markets and slaughterhouses in Turkey.…”
Section: Resultssupporting
confidence: 73%
“…In addition, 8 of the 12 samples contained the actA and hlyA genes. It has been reported that differences in the prevalence of virulence genes may be related to the use of several PCR target fragments within the genes (Coban et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Very few data are available at the European level on L. monocytogenes CCs and WGS analysis in poultry. Most of the existing studies have used old typing techniques such as serotyping and PFGE [ 5 , 6 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of chicken meat and foods prepared using chicken meat can occur at various stages before marketing, including the primary production stage, abattoir, processing plant, and retail stores [ 5 ]. In recent years, numerous studies on the presence of L. monocytogenes in these matrices have been conducted worldwide [ 5 , 6 , 7 , 8 , 9 ]. The consumption of cooked chicken products was previously associated with the transmission of listeriosis and caused several listeriosis outbreaks in different countries [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%